2016
DOI: 10.46743/2160-3715/2016.2387
|View full text |Cite
|
Sign up to set email alerts
|

Using a Non-Judgmental Stance to Promote Trustworthiness in Action Research

Abstract: This article describes the use of action research to increase trustworthiness through a non-judgmental approach. Two foreign language lecturers implemented an action research to improve their teaching with the use of Facebook and mobile devices. In order to remain open to all possible interpretation of the events and to incite their students to provide them with honest feedback, they openly adopted a non-judgmental stance. As a result, students freely revealed how they used funds which were given to them to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For these reasons, the authors opted for a critical review over a meta-analysis. Following the approach advocated by Gabarre et al (2021), the authors organised the literature review by conducting a critical review of studies on the implementation of ICT to enhance ELT". Guzzo et al (1987) suggested approaching the task of conducting a critical review in the same fashion as a quantitative study.…”
Section: Critical Reviewmentioning
confidence: 99%
“…For these reasons, the authors opted for a critical review over a meta-analysis. Following the approach advocated by Gabarre et al (2021), the authors organised the literature review by conducting a critical review of studies on the implementation of ICT to enhance ELT". Guzzo et al (1987) suggested approaching the task of conducting a critical review in the same fashion as a quantitative study.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Another important aspect of understanding positionality in research is being non-judgmental. This approach helps researchers to build truthworthiness which adds reliability to the research [15]. As the researcher was not part of their caste, it was perceived by participants that the researcher may not be able to understand and/or be judgmental when talking discrimination, they face from higher caste groups.…”
Section: Researchermentioning
confidence: 99%
“…At [22] enabled the equitable participation of all participants in the round table discussions. Table facilitators recorded the main points of argumentation articulated in each round of discussion and shared the outcomes of prior rounds for further discussion with each new group as participants moved between tables and topics for further discussion and clarification.…”
Section: Part 2: World Café Style Consensus Workhopmentioning
confidence: 99%
“…Consensus workshop data collection ceased upon workshop completion. A non-judgmental stance [22] towards all perspectives was taken throughout the study. Modified Delphi questionnaire themes and statements emerged iteratively from the physician interviews, unpublished systematic literature review, and previously published work on nurses, residents and family perspectives on how to improve a supportive approach to end-of-life care in LTC Equitable facilitation techniques were deployed in the workshop discussions.…”
Section: Part 2: World Café Style Consensus Workhopmentioning
confidence: 99%